MUC1 and carbohydrate associated antigens in head and neck squamous cell carcinoma: our experience - Croce, María Virginia (2018)
Head and neck cancer constitutes the sixth cause of cancer worldwide with an age-standardized rate of 9.1 cases per 100,000 inhabitants, not including thyroid tumors. Most stage I/II patients have a very good prognosis while those with higher stages of the disease show a poor overall survival being the presence of lymph node metastases the main factor. Development of tumor markers either prognostic as well as to detect early recurrences or therapy-predictive would have critical importance. In the last years, several publications related to immunotherap, genomics and viral carcinogenesis have explored new biological targets and markers for this disease.